INTERAKSI SOSIAL WARGA BELAJAR PAKET C DI PKBM BUNGA TANJUNG DESA TANJUNG RAMBUTAN KECAMATAN KAMPAR KABUPATEN KAMPAR - Fitri Amelia; Aswandi Bahar; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is descriptive with quantitative approach which reflects the result of research with the numbers. The sampling technique used simple random sampling technique (random sampling). Technique of data retrieval in this research is by technique of questionnaire, which pointed 72 item statement. The data were obtained from respondents entitled 20 people for the experimental sample and 38 people for the research sample. After the questionnaire was tested, there were 4 invalid items, and the researcher pulled out all that was not, the overall instrument trusted with Alpha Cronbach = 0.99. The results of the above research, affecting the indicator it can be concluded that the indicators can be defend well. Cooperation is a collective work between individuals or groups of people to achieve one or more common goals, Competition or competition can be defined as a social process, in which individuals or groups of people compete, seek profit through the areas of life that occurred in the future certain happened. It is disputes or disputes (hereinafter referred to as contradictions) committed by persons or groups that commit violence and / or violence. Keywords: Social Interaction of Citizens Learning Package C